At Risk or in Danger, in Need or with Requirements? On the discursive simultaneity of contradictory ideas in the course of the development of educational projects in context of International Organisations - Kiuppis, Florian (Swiss Journal of Educational Research, 2018)
The text deals with a case of the transformation of knowledge which reflects «translations of ideas» in the context of negotiations during the development of a project for disadvantaged children and youths, run by the Center for Educational Research and Innovation (OECD). The focus is on the project «Children and Youth at Risk», carried out throughout the 1990´s, and connected with the goal to guarantee access to education for those learners considered most disadvantaged: primarily children and youth living in poverty, and/or belonging to ethnic minorities. Data is drawn from archival documents gathered in the OECD Headquarters in Paris. Method applied is content analysis.